OPPORTUNITIES FOR THE DEVELOPMENT OF CULTURAL AND EDUCATIONAL TOURISM AS A PERSPECTIVE FOR THE PRESERVATION AND USE OF THE CULTURAL HERITAGE OF THE MOSTOVSKY DISTRICT OF THE KRASNODAR REGION - Мещанинова, Елена (Вестник ЗКУ, 2022)
The issues of preservation and use of cultural heritage objects are one of the priority tasks facing many regions of the Russian Federation. The most effective solution to this problem is cultural and educational tourism, the development of which contributes to the protection and maintenance of objects of culture and archaeology. The Mostovsky district of the Krasnodar Territory has a rich archaeological heritage: 564 dolmens, the remains of ancient fortresses, ancient inscriptions on open rocks, stones, in places of ancient human settlements, on caravan routes, on the walls and ceilings of caves, in deep gorges. The article provides an analysis of cultural heritage objects on the territory of the Bagovsky rural settlement of the Mostovsky district,